Protestant Bible Education for Women: First Steps in Professional Education for Modern Korean Women - Strawn, Lee-Ellen (Journal of Korean religions, 2013)
Bible education in the Korean Protestant Church is a notable strain of modern education for women in the early twentieth century. Not only did these opportunities provide many Korean women with basic literacy skills, but the advanced training for certified Bible Woman status represented the initial steps in women’s professional education. Such professional education of Bible Women, open to women from all walks of life, was an avenue for self-betterment, professional transformation and social mobility. With a focus on theological and practical training, Bible classes, Bible institutes and Bible training schools provided women with heretofore unavailable opportunities to meet publicly with women of diverse backgrounds and to be taught and led by Korean women. Bible classes provided some of the first opportunities for professional female leadership in modern Korea and thus they portrayed a pattern of transmission of the Bible both for and by Korean women. In this way, Bible education for women deserves to be recognized as the first steps in women’s leadership and professional education in modern Korean society.